(untitled) (Gaceta Técnica, 2019)
The architecture, engineering and construction industry has great activity and importance, it moves other areas to satisfy the infrastructure needs of most economic and social activities, such as housing, roads, education, industry and health, among others However, it is one of the industries with the lowest productivity and which seems not to have taken advantage, as do other production sectors in general, of the opportunities offered by some management philosophies to solve complications and difficulties. This article analyzes the most relevant lessons learned from the implementation, both in the previous phases and in the link or relations between them, and in the corporate area of the company, when applying the constructablity in the planning stages, design and acquisitions, guiding the objectives of multidisciplinary teams towards the integration of a housing project built in Barquisimeto, Venezuela. The methodology was used in the integral process of the project, prior to the preliminary project, which led to the continuation of benefits in costs, times and quality of the final product in a pilot project